Development of Arabic case system online tutorial using screen capture software - Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri (INSI Publications, 2014)
In recent years, online tutorials have become well-established tools for the delivery of information literacy training as information professionals continue to seek new and more effective ways to reach audiences. This paper focuses on a project at the Quranic Language Department (QLD), International Islamic University of Malaysia to develop a new approach to online instruction. The goals of the project were to explore how the addition of video using screen capture might create a more engaging user experience, and how the online video tutorial might therefore both improve existing information literacy training as well as offering a „just-in-time‟ point of support. This paper researches the practical steps involved in creating useful and accessible online tutorials for Arabic Case System lessons. In order to examine the efficacy of this tool, students from Advance Arabic level were tested with formative test related to Arabic Case System topics. The result demonstrates that screen capture can enhance students‟ performance and maximise the impact of e-learning tools, helping online tutorials to deliver information in a more personal and immediate way.